Orthodontic treatment of an adolescent patient with Class II division 1 malocclusion with consideration of growth pattern and occlusal plane: A case report. Issue 5 (15th May 2021) - Hou, Jianhua; Sun, Mengyao; Meng, Xiuping
Key Clinical Message: Consideration of growth pattern and occlusal plane is critical in orthodontic treatment planning to achieve optimal dentofacial esthetics and long‐term stability in adolescent patients, which is illustrated by success in orthodontic treatment of an adolescent Class II division 1 malocclusion with nonextraction. Abstract : Consideration of growth pattern and occlusal plane is critical in orthodontic treatment planning to achieve optimal dentofacial esthetics and long‐term stability in adolescent patients, which is illustrated by success in orthodontic treatment of an adolescent Class II division 1 malocclusion with nonextraction.